New challenges in the administration of justice: The use of information and communication technologies - Yépez Provincia, Lizbeth Nohemi (2022)
As in the case of every human product in our society, the administration of justice in Peru has undergone changes over the years. During the past decade, these changes have increased exponentially due to the different technological breakthroughs and their implementation in the administration of justice in Peru. Hence, this article seeks to identify the main challenges being faced by the administration of justice in this implementation process and to find possible solutions.